DRG Center practical tips to implement more context-adaptive programming - Jacobstein, David (#AdaptDev, 2018)
Hi #adaptdevers, The cross-sectoral programs team in the DRG Center have been working in support of ways that programming can be made more aware of, and responsive to, context considerations that have to do with incentives and relationships between different actors - often called power dynamics or political economy. Following several discussions with field folks, we were asked to come up with simple and practical tips that could help staff to implement more context-adaptive programming, or to better Work Politically to use TWP jargon. With assistance from many of our field staff and partners, we've put together three documents (to start) that have now been cleared to share publicly: • Tips on Making Your Solicitations Invite Context-Driven Adaptive Programming - suggestions spanning most sections of a typical solicitation to better weave in Thinking and Working Politically. I'm particularly excited that this document contains embedded links to excerpts from a set of solicitations that model good practice. You can also find a summary of all the excerpts from real solicitations, and links onward to the public posting of those solicitations on Fed Biz Ops or Grants.gov, here. • Tips on Power Dynamics and Theories of Change - suggestions relevant to those working on project designs and logic models. • Tips for Better Use of Advisory Councils - suggestions to set up better advisory bodies that help you to incorporate political economy more automatically into your programmatic adjustments. I hope that you'll find these practical and helpful! Feedback is always welcome. Best, David

How are Research for Development Programmes Implementing and Evaluating Equitable Partnerships to Address Power Asymmetries? - Snijder, Mieke; Steege, Rosie; Callander, Michelle; Wahome, Michel; Rahman, M. Feisal; Apgar, Marina; Theobald, Sally; Bracken, Louise J.; Dean, Laura; Mansaray, Bintu; Saligram, Prasanna; Garimella, Surekha; et al. (The European Journal of Development Research, 2023)
The complexity of issues addressed by research for development (R4D) requires collaborations between partners from a range of disciplines and cultural contexts. Power asymmetries within such partnerships may obstruct the fair distribution of resources, responsibilities and benefits across all partners. This paper presents a cross-case analysis of five R4D partnership evaluations, their methods and how they unearthed and addressed power asymmetries. It contributes to the field of R4D partnership evaluations by detailing approaches and methods employed to evaluate these partnerships. Theory-based evaluations deepened understandings of how equitable partnerships contribute to R4D generating impact and centring the relational side of R4D. Participatory approaches that involved all partners in developing and evaluating partnership principles ensured contextually appropriate definitions and a focus on what partners value.